Core Europe and the United Kingdom: Risks, opportunities and side-effects of the British reform proposals - Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2016)
The EU is in the midst of completing one of its most delicate negotiations to date - the talks on the "EU Reform" with which British Prime Minister David Cameron hopes to persuade the British to vote to stay in the Union. The heart of his vision for the EU is flexibility. Britain should be given the opportunity to cut loose from further EU integration and concentrate its membership on a deepened internal market. As such, Cameron is proposing to consolidate his nation's existing special position within an increasingly differentiating Union. Concrete political considerations aside, the EU states must therefore find answers to two central questions in the negotiations: How much differentiation, how many opt-outs, can the European Union withstand? And how can a single market of 28, a Eurozone of 19 and more permanent differentiation be better managed? (SWP Comments)
Keywords: 320